India-China Maritime Competition: The Security Dilemma at Sea, 1st edition - Basrur, Rajesh (Routledge, 2020)
This edited volume critically examines the concept of the “security dilemma” and applies it to India–China maritime competition. Though frequently employed in academic discussion and popular commentary on the Sino-Indian relationship, the term has rarely been critically analysed. The volume addresses the gap by examining whether the security dilemma is a useful concept in explaining the naval and foreign policy strategies of India and China. China’s Belt and Road Initiative and its expansive engagement in the Indian Ocean Region have resulted in India significantly scaling up investment in its navy, adding ships, naval aircraft and submarines. This volume investigates how the rivalry is playing out in different sub-regions of the Indian Ocean, and the responses of other powers, notably the United States and prominent Southeast Asian states. Their reactions to the Sino-Indian rivalry are an underexplored topic and the chapters in this book reveal how they selectively use that rivalry while trying to steer clear of making definite choices. The book concludes with recommendations on mitigating the security dilemma.